Integrating whole-genome re-sequencing and transcriptome data to reveal the molecular mechanism of TBX5 gene regulating feathered feet in Guangxi native chickens - Zhuliang Yang; Yongcui Liu; Jintang Luo; Cong Xiao; Hong Yuan; Wenya Du; Xiurong Yang (Poultry Science)
Feathered foot is a trait observed in domestic and wild chickens, resulting from the partial or complete transformation of scales on the tarsus, shanks, and toes into feathers. Although previous studies have mapped genomic loci associated with feathered feet, the molecular mechanisms underlying this transformation remain unclear. This study combined whole-genome re-sequencing (WGS) data, transcriptomic analysis, and cellular experiments to investigate the genetic basis of feathered feet in Guangxi native chickens. A genome-wide association study (GWAS) involving 1,735 Guangxi native chickens identified two genomic regions and several candidate genes, including TBX3, TBX5, and H2AFY. RNA sequencing (RNA-seq) and real-time fluorescent quantitative PCR (QRT-PCR) results confirmed that TBX5 is differentially expressed between chickens with scaled and feathered feet, indicating its role as a key candidate gene for feathered feet. The function of TBX5 was subsequently explored at the cellular level using chicken dermal fibroblasts. The results showed that moderate overexpression of TBX5 (20 ng) significantly increased the expression of cell proliferation-related genes. In contrast, excessive overexpression of TBX5 (2.5 μg) and interference with TBX5 inhibited these genes, suggesting a dose-dependent effect of TBX5 on the proliferation of dermal fibroblasts. EdU fluorescence staining, flow cytometry, and migration assays demonstrated that moderate expression of TBX5 can promote the proliferation and migration of dermal fibroblasts, while TBX5 interference produced opposite results. Our findings suggest that TBX5 is a pivotal candidate gene associated with feathered feet in Guangxi native chickens. It is proposed that TBX5 may affect the formation of feathered feet by regulating the proliferation and migration of dermal fibroblasts.